SPECIAL OPERATIONS FORCES OF THE ARMED FORCES OF THE REPUBLIC OF UZBEEKISTAN: IN THE PAST, AT PRESENT, IN THE FUTURE (American Journal of Pedagogical and Educational Research, 2024)
This article analyzes retrospectives and current state of the SOF of the Armed Forces of the Republic of Uzbekistan in comparison with the Special Operations Forces units’ organization and experience of use in the leading foreign armies of the world.